Nonmedical Cannabis Use: Patterns and Correlates of Use, Exposure, and Harm, and Cancer Risk. Issue 58 (27th November 2021) - Cohn, Amy M; Blount, Benjamin C; Hashibe, Mia
Abstract: Cannabis has certain health benefits, but some people may experience harms from use. Co-use of tobacco and cannabis is common. Smoke from cannabis contains many of the same carcinogens and toxicants as the smoke from tobacco, raising concerns that cannabis smoking may be a risk factor for cancer. With growing access to and acceptance of medical and nonmedical cannabis, there is an urgent need to understand the risks and benefits of the current modes of cannabis use and how cannabis may be associated with cancer risk. This monograph summarizes a session from a National Cancer Institute Symposium on nonmedical cannabis use and cancer risk. We had 3 objectives: describe the relation between nonmedical cannabis use and cancer risk, delineate patterns and correlates of cannabis co-use with tobacco, and document potentially harmful inhalational exposure resulting from smoked and vaped cannabis. Methodological limitations in the literature and future research recommendations are provided.